2009
DOI: 10.1007/s10519-009-9310-z
|View full text |Cite
|
Sign up to set email alerts
|

Do Nightmares and Generalized Anxiety Disorder in Childhood and Adolescence have a Common Genetic Origin?

Abstract: The present study investigated the prevalence and heritability of nightmares and their comorbidity with psychopathology in a sample (N = 1,318) of children, adolescents, and child and adolescent twins ranging in age from 4 to 17 years old. The prevalence of terrible nightmares was estimated to be 6.4%, which is similar to previous studies. There were marginal gender differences in this rate (7.7% for boys; 5.1% in girls), contrary to previous studies that purport higher rates for girls. There was little eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 21 publications
5
30
0
1
Order By: Relevance
“…It has also been suggested that at least some of the relationship between GAD and nightmares might be caused by common genes, although the 2 conditions have largely independent genetic influences. 47 In accordance with earlier studies of school children, 48 the current findings suggest sleep disorder to be more strongly associated with symptoms of anxiety than symptoms of depression in young children. Notably, however, anxiety is an early-onset disorder, whereas depression usually occurs later in life; in addition, anxiety is often a precursor to later depression.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been suggested that at least some of the relationship between GAD and nightmares might be caused by common genes, although the 2 conditions have largely independent genetic influences. 47 In accordance with earlier studies of school children, 48 the current findings suggest sleep disorder to be more strongly associated with symptoms of anxiety than symptoms of depression in young children. Notably, however, anxiety is an early-onset disorder, whereas depression usually occurs later in life; in addition, anxiety is often a precursor to later depression.…”
Section: Discussionsupporting
confidence: 91%
“…The continuity hypothesis, in relation to nightmares, has been supported by previous empirical findings that found associations between the experience of nightmares and unpleasant and/or unusual waking experiences such as dissociative tendencies (Cheung, 2012), trauma (Nadorff, Nazem, & Fiske, 2011), schizotypal traits (Watson, 2001), depression and suicidality (Cukrowicz et al, 2006), anxiety (Coolidge, Segal, Coolidge, Spinath, & Gottschling, 2010), and general psychological distress symptoms (Levin & Fireman, 2001). In addition to what might be considered unpleasant psychological states noted previously, a consistent finding of previous studies has been that nightmares were related to unpleasant trait psychological experiences.…”
Section: Original Articlementioning
confidence: 82%
“…Previous findings that parasomnias are related to emotional problems such as a child' s daytime anxiety 46,47 and behavioral problems 22 indicate that stress may be an important mechanism for the association between being bullied and parasomnias. Firstly, being bullied and in particular, chronic victimization, might create a sense of learned helplessness, 48 making this subgroup more vulnerable to stress symptoms.…”
Section: Discussionmentioning
confidence: 99%